Homoisopogon a from Ophiopogon japonicus induces apoptosis in A549 – a non small cell lung cancer cell line - Chung, Nguyen Dinh; Dat, Nguyen Tien; Anh, Le Thi Van; Lee, Jeong-Hyung; Dang, Nguyen Hai (Vietnam Journal of Biotechnology, 2018)
Lung cancer is the leading cause of death among Vietnamese people and can be divided into two major groups: small cell lung cancer (SCLC), and non-small cell lung cancer (NSCLC). It is estimated that 85% of patients was diagnosed as NSCLC. Therapy drugs that targeted lung cancer tumors with the epidermal growth factor receptor (EGFR) may initially provide benefit, but over time tumors can develop resistance. The recent discovery of EGFR-tyrosine kinase inhibitors (EGFR-TKIs) has provided a new target for the theurapeutic agents in non-small cell lung cancer treatment. In our study, homoisopogon A, a new compound isolated from the tubers of Ophiopogon japonicus (Mach mon, in Vietnamese) effectively showed the cytotoxic activity to the EGFR and TKI-resistant NSCLC cell lines including human lung carcinoma A549, human lung adenocarcinoma NCI-H1975 and human lung adenocarcinoma NCI-H1650. The IC50 values of homoisopogon A against A549, NCI-H1975 and NCI-H1650 were determined as 6.26, 19.51, and 24.66 µM, respectively. Preliminary study on the mechanism of action using flow cytometry analysis was performed. Homoisopogon A treatment of A549 cells at concentration of 25 μM generated apoptosis in 27.5% of cells (7% early apoptosis and 20.5% late apoptosis) after 24h of treatment. The effect increased significantly at the concentration of 50 μM, the homoisoflavanone generated apoptosis in 83.8% of cells (23.5% early apoptosis and 60.3% late apoptosis). Treatment with homoisopogon A for 48h also resulted in typical apoptotic morphological changes in A549 cells under microscopic observation. The results strongly suggested that homoisopogon A induces apoptosis in EGFR and TKI-resistant-A549 cells, thus resulting in the cytotoxicity